“O melhor e mais obediente filho” - Tiago Viúla de Faria (Medievalista)
From about 1412, infante Duarte, Portugal’s heir apparent, took on a large portion of the roles expected of a king, until 1433, the year he finally came to the throne. For two decades, his father, King João I – already a seasoned sovereign – had come to rely on the firstborn to assist him in the everyday management of royal administration, justice, and certain economic matters. This was to become known to historians as the prince–king “association”. This essay departs from an interrogation, of whether Duarte was able – or expected at all – to play a role of his own in diplomatic affairs. My argument takes into account Duarte’s posturing as the first in the line of succession, his position as one of several siblings in a tightly knit dynasty, and his own realisations in external politics. The documentary evidence surrounding several treaties involving Aragon, Castile and Navarre seems to point to Duarte’s restraint as a diplomatic player in his own right, even during the “association” period before he became king. For the most part, he remained subordinate to a dynastic logic, with his father firmly hanging on to the helm.